Laboratory blood group examination of proteolysis degradation human blood - Beta Ahlam Gizela Beta Ahlam Gizela (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Blood group examination has many purposes and one of them is identification. In several forensic cases there is incompatibility of blood group in corpse and in other evidences usually used blood group examination is serum agglutination method. From the previous study, it was found that there was increasing osmotic fragility of red cell. For that reason, we need to know how the result of blood group tests in degradation human blood.Objective: The purpose of this study is to know blood groups of proteolysis degradation human blood.Method: This study was an experimental study. The subjects was people that have blood group A, B, AB, and 0. Blood samples were examined serially for blood grouping, when the samples were just taken, after stored in room temperature, with addition of protease enzyme (tripsin) in 20 seconds, 1 hour, 2 hours, 3 hours, and 24 hours, and without protease enzyme after 7 days. The data was analysed using chi-square statistics.Result: This study showed there was significant proportionally different(p<0.05) in blood group chang-ing of non-0 blood group to be 0 blood group after stored the blood in 3 hours with protease enzyme addition (5(16.68%)). In 24 hours, it was showed that all of non-0 blood group changed to 0 blood group (100%). Blood group examination of the blood without protease enzyme addition stored for 7 days showed that all of them were observed as 0 blood group.Conclusion: There is blood group changing by agglutination method from non-O blood group to 0 blood group in proteolysis degradation blood. Key words: blood group - proteolysis degradation - group changing